2004
DOI: 10.1177/0145482x0409801006
|View full text |Cite
|
Sign up to set email alerts
|

Policy to Practice: Teachers’ and Administrators'Views on Curricular Access by Students with Low Vision

Abstract: This national study reviews national and state policies and guidelines, as well as surveys and focus groups of administrators and teachers, on the implementation of policies for students with low vision to gain visual access to the general education curriculum. The findings demonstrate that few states provide the necessary services to enable students to achieve access and that people, philosophy, and systems are the main impediments to and the solutions for change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…However, despite extra parental attention at home, lack of accessible materials would likely be associated with lower achievement scores. Unfortunately, students who require Braille or large-print textbooks and other school materials often do not receive them, receive them much later than the other students, (e.g., Corn & Wall, 2002; Smith, Geruschat, & Huebner, 2004), or receive material of inferior quality (Herzberg & Stough, 2009). If the student with a VI cannot independently access his or her homework or mathematics book, parents will be required to assist with homework.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite extra parental attention at home, lack of accessible materials would likely be associated with lower achievement scores. Unfortunately, students who require Braille or large-print textbooks and other school materials often do not receive them, receive them much later than the other students, (e.g., Corn & Wall, 2002; Smith, Geruschat, & Huebner, 2004), or receive material of inferior quality (Herzberg & Stough, 2009). If the student with a VI cannot independently access his or her homework or mathematics book, parents will be required to assist with homework.…”
Section: Discussionmentioning
confidence: 99%
“…The need to change these aspects is in line with the recommendations of the International Council for Education of People with Visual Impairment and the World Blind Union (2003) and the American Foundation for the Blind (2005), as well as with analyses in other studies. These studies emphasized the need for resources and support that are suited to the specific needs of students with visual impairments (Davis & Hopwood, 2002;Gray, 2009;Smith et al, 2004) and the importance of having well-informed and well-coordinated professionals (Davis & Hopwood, 2002;Gray, 2005Gray, , 2009. In Spain, the resources are widely provided by ONCE.…”
Section: Discussionmentioning
confidence: 99%
“…(i.e., west, midwest, northeast, south) (Abner & Lahm, 2002;Behrmann, 1993;Derer, Polsgrave, & Rieth, 1996;Howard, 1992;Kapperman, Sticken, & Heinze, 2002;Lesar, 1998;McGregor & Pachuski, 1996;Wahl, 2004), collectively they fail to provide the same information for each of those regions. Several studies involve students from only two of the disability categories found in IDEIA 2004 (Abner & Lahm, 2002;Corn & Wall, 2002;Edwards & Lewis, 1998;Kapperman et al, 2002;Skellenger, 1999;Smith, Geruschat, & Huebner, 2004;Wehmeyer, 1998Wehmeyer, , 1999. Secondary students are virtually ignored (Abner & Lahm, 2002;Edwards & Lewis, 1998;McGregor & Pachuski, 1996;Skellenger, 1999;Wehmeyer, 1998Wehmeyer, , 1999.…”
mentioning
confidence: 99%